Kedudukan Hukum Pidana Terhadap Pelaku Tindak Pidana Narkotika Jenis Shabu-Shabu - Immanuel Simanjuntak; Emmanuella Mary Oktavia Lumbantobing; Immanuel Pahala Surya Lumbantobing; Geby Teresy Apriani Sihombing (Jurnal Hukum Lex Generalis, 2025)
Narcotic crimes have a profound impact on both society and the state. Law enforcement against offenders, particularly those involving methamphetamine, is based on Law No. 35 of 2009 on Narcotics. In Decision No. 3590/Pid.Sus/2021/PN.Mdn, the defendant was found guilty of possessing and distributing methamphetamine and was sentenced to eight years of imprisonment along with a fine of IDR 800 million in accordance with Article 112 paragraph (1) of the aforementioned law. This study employs a normative juridical approach to analyze the legal position of the offender and the application of criminal sanctions. Active participation from both law enforcement authorities and the public is essential in combating narcotics in order to create a deterrent effect and establish consistent jurisprudence. Strengthening collaboration between law enforcement agencies and society is crucial for preventing and eradicating drug trafficking. Furthermore, legal sanctions should be imposed firmly and proportionally to deter future offenses and to serve as a legal precedent in similar cases.